The Effect of Various Types of Mulch on the Growth and Yield of Dayak Onions (Eleutherine palmifolia (L.) Merr) - Rahmat Hidayat; Hilda Susanti; Dewi Erika Adriani (TROPICAL WETLAND JOURNAL, 2019)
The research on the effect of various types of mulch on the growth and yield of Dayak onions (Eleutherine palmifolia (L.) Merr) has been carried out in the field at Al-Ikhwan complex, Banjarbaru City, South Kalimantan in March until July 2019. This research used a completely randomized design (CRD) single factor with 4 types of mulch treatment; m0 = without mulch, m1 = silver black plastic mulch, m2 = rice straw mulch, m3 = water hyacinth mulch, then repeated 3 times, thus 12 units of plot experiment. Each experimental unit contained 20 plants, with 6 sampling plant for observation. The parameters observed in this study were plant height, number of leaves, number of tillers, time of first flower appearance, number of bulb, and total fresh weight of bulb. The results showed that the treatment of various types of mulch could not affect the growth and yield of Dayak onions and there was not available the best type of mulch on the growth and yield of Dayak onions.